2015
DOI: 10.1055/s-0034-1398850
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hybrid Iterative Reconstruction on Agatston Coronary Artery Calcium Scores in Comparison to Filtered Back Projection in Native Cardiac CT

Abstract: Purpose: To investigate whether the effects of hybrid iterative reconstruction (HIR) on coronary artery calcium (CAC) measurements using the Agatston score lead to changes in assignment of patients to cardiovascular risk groups compared to filtered back projection (FBP). Materials and Methods: 68 patients (mean age 61.5 years; 48 male; 20 female) underwent prospectively ECG-gated, non-enhanced, cardiac 256-MSCT for coronary calcium scoring. Scanning parameters were as follows: Tube voltage, 120 kV; Mean tube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
(25 reference statements)
2
9
0
Order By: Relevance
“…28 A further study has recently shown the excellent correlation of clinical risk groups between FBP and hybrid IR at full-dose scanning. 29 In the present study, there remained excellent agreement of absolute and percentile risk scores with the reference technique (FBP at normal dose settings) when using AIDR-3D mild at a tube current as low as 25%. The patients who were reclassified with AIDR-3D mild were the result of small absolute changes in Agatston scores in patients who were either on the borderline between categories or relatively young, so that a small absolute change resulted in reclassification.…”
Section: Discussionsupporting
confidence: 69%
“…28 A further study has recently shown the excellent correlation of clinical risk groups between FBP and hybrid IR at full-dose scanning. 29 In the present study, there remained excellent agreement of absolute and percentile risk scores with the reference technique (FBP at normal dose settings) when using AIDR-3D mild at a tube current as low as 25%. The patients who were reclassified with AIDR-3D mild were the result of small absolute changes in Agatston scores in patients who were either on the borderline between categories or relatively young, so that a small absolute change resulted in reclassification.…”
Section: Discussionsupporting
confidence: 69%
“…Phantom studies also showed a trend towards lower Agatston scores using IR [8,13,21]. The results of patient studies comparing FBP and IR in standard dose CAC scoring are equivocal with significant reduction in Agatston scores and only slight reduction of Agatston scores, respectively [11,12,15,16,22]. The noise related over-blooming effect in calcifications causes overestimation of the score values.…”
Section: Discussionmentioning
confidence: 99%
“…At present, an iterative reconstruction (IR) technique is able to reduce image noise [8,9]. Some phantom studies as well as patient studies have shown comparable Agatston scores comparing IR with the standard filtered backprojection (FBP) technique using identical image data [10][11][12]. In contrast, other studies have indicated minor differences or significant differences with underestimation of Agatston scores and calcium volume scores, respectively [8,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous publications, all using multi-row single source CT, have discussed the benefits and pitfalls of different IR algorithms for noise and dose reduction in CAC evaluation. In particular, the publications on hybrid IR algorithms and model-based IR (iDose4 and IMR, Phillips Healthcare, Best, The Netherlands), as well as adaptive iterative dose reduction algorithms (AIDR 3D, Toshiba Corp. Medical Systems, Tokyo, Japan) attract attention (6,10,2224). IR algorithms allow for a significant reduction in image noise and could allow for substantial reduction in radiation dose while maintaining diagnostic accuracy as has been previously shown for other vendors than the one in the present study (22,25,26).…”
Section: Discussionmentioning
confidence: 99%